50 gastrointestinal cases and associated imaging - Shaikh, Abdullah A. (Tfm Pub., 2013)
Medical students and junior doctors are an integral part of the healthcare system. On an academic gastroenterology service, they often initially evaluate the patients that are then staffed by the consulting physician. Like all clinical specialties, the acquisition of medical knowledge is required to gain expertise. There are several resources such as textbooks and evidence-based articles that are available for this purpose.